2015
DOI: 10.1071/wf13099
|View full text |Cite
|
Sign up to set email alerts
|

Live fuel moisture content and leaf ignition of forest species in Andean Patagonia, Argentina

Abstract: Wildfires are common from summer to early fall in Patagonian forests of Argentina. Live fuel moisture content (LFMC) and leaf ignition are important factors for understanding fire behaviour. In this study, we determined seasonal LFMC and leaf ignition of some key fire-prone species of these forests, and their relationships with environmental variables. Species investigated were the native trees ñire (Nothofagus antarctica) and cypress (Austrocedrus chilensis), the understorey tree-like radal (Lomatia hirsuta) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(53 reference statements)
0
19
0
3
Order By: Relevance
“…). For example, lower leaf water content and lower LMA are associated with faster leaf ignition (Bianchi and Defossé , Grootemaat et al. ), while higher LMA and larger leaf area (LA) are related to longer duration of leaf burn (Grootemaat et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). For example, lower leaf water content and lower LMA are associated with faster leaf ignition (Bianchi and Defossé , Grootemaat et al. ), while higher LMA and larger leaf area (LA) are related to longer duration of leaf burn (Grootemaat et al.…”
Section: Introductionmentioning
confidence: 99%
“…While landscape variation among species in traits such as LMA is driven largely by environmental gradients, laboratory studies have also found to varying degrees that interspecific variation in leaf traits can often be a predictor of variation in leaf flammability (Gill and Moore 1996, Ganteaume et al 2013, Murray et al 2013, Grootemaat et al 2015. For example, lower leaf water content and lower LMA are associated with faster leaf ignition (Bianchi andDefoss e 2015, Grootemaat et al 2015), while higher LMA and larger leaf area (LA) are related to longer duration of leaf burn (Grootemaat et al 2015). What has yet to be considered, however, is the possibility that if leaf traits are found to vary among species as a function of environmental conditions across a landscape, with these traits in turn driving differences among species in leaf flammability, then landscape variation in leaf level flammability might be largely predictable on the basis of variation in a few key leaf traits responding to environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…(); White & Zipperer (); Blackhall, Raffaele & Veblen (); Cóbar‐Carranza et al . (); Bianchi & Defossé (); Blackhall, Veblen & Raffaele ().…”
Section: Introductionmentioning
confidence: 99%
“…Leaves were harvested at 2-m height on north aspect (Bianchi and Defossé 2015). The compositions of the mixed samples (i.e.…”
Section: Biodiversity: Shannon Index Plant Cover Richnessmentioning
confidence: 99%